2020
DOI: 10.1080/0142159x.2020.1804056
|View full text |Cite
|
Sign up to set email alerts
|

Traveling by winding roads or highways: Stability of medical students’ specialty preferences over time

Abstract: Introduction: Medical students switch career preferences during medical school and likely distinguish themselves in stability of preference over time. The purpose of our study was to gain insight in career paths stability of medical students. Method: The authors conducted a longitudinal, four sessions interview study with medical students with three intervals over a three and a half-year period. From all 24 participants the first and second career preferences were documented, analyzed and we calculated a stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…We identified the moments when career intentions changed, thus expanding on previous evidence that career intentions change between matriculation and graduation [ 37 ]. These findings are in line with those from a recently published study of specialty preferences in a small student cohort in the Netherlands [ 38 ], which observed that career preference paths were unstable in subgroups of students. In our cohort, most changes occurred during the clinical years, suggesting that clinical experiences might have influenced career intentions [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…We identified the moments when career intentions changed, thus expanding on previous evidence that career intentions change between matriculation and graduation [ 37 ]. These findings are in line with those from a recently published study of specialty preferences in a small student cohort in the Netherlands [ 38 ], which observed that career preference paths were unstable in subgroups of students. In our cohort, most changes occurred during the clinical years, suggesting that clinical experiences might have influenced career intentions [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…Recent qualitative evidence from studies about early career doctors reveals that early career doctors go through a complex and dynamic process in determining their chosen specialty [17]; however, quantitative evidence about this process could be complementary for informing policy. Most evidence about specialty decisions and their timing is largely centred on medical students, demonstrating how specialty choice intention can vary yearto-year over the course of medical school training [18][19][20][21][22]. An Australian study found that 76% of medical students changed their first preference specialty from commencement to exit from medical school [23].…”
Section: Introductionmentioning
confidence: 99%
“…Our study is based on a theoretical framework of medical student career choice [ 6 ] and draws inspiration from and expands on a previously published study quantifying career intention stability [ 11 ]. To our knowledge, this is the first study using a large cohort to describe career intention dynamics using more than two time points, to quantify career intention indecision, and to test associations with other variables.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these motives remained stable over a four-year period, suggesting that they might be related to students’ intrinsic characteristics and thus be important factors to consider when studying the development of career choices. Other authors explored career intentions in a cohort of 24 students, developing a score quantifying career intention stability [ 11 ]. Their findings suggested three trajectories: students with stable career intentions; students considering two or three options; and students with unstable preferences.…”
Section: Introductionmentioning
confidence: 99%